Analisis Kandungan Vitamin C, Serat Kasar Dan Daya Terima Jus Rosella (Hibiscus sabdarrifa L.) Sebagai Alternatif Minuman Kesehatan Penderita Diabetes Melitus - Nany Suryani; Oklivia Libri; Mita Dwi Lestina (HB PRESS, 2019)
Diabetes mellitus is a chronic disease that requires strategy and treatment. One of the treatments is by administering pharmacological therapies such as herbal therapies. In this study, herbal therapies that can be used as an alternative are instant Rosella juice. Rosella has vitamin C and coarse fiber which is beneficial to lower blood sugar content. The purpose of this research is to analyze the content of vitamin C, crude fiber and the receiving power of Rosella juice (Hibiscus sabdariffa L) as an alternative to diabetes mellitus health drink sufferer. This research is purely experimental research with complete randomized draft research design. In the study conducted a test of vitamin C and coarse fiber by comparison of the proportion of instant Rosella and water (1:25, 1:50 and 1:75). To see the juice received the Hedonic test by involving 25 panelists. Based on the research results the highest content of vitamin C Rosella is 0,03%/300 mg and the highest crude fiber is 23,45 g. One way Anova analysis says that there is a proportion to the influence of vitamin C (p=0,009) and there is an influence of proportion to Crude fiber content (p = 0,000). Friedman's analysis of the receiving power is (color (p = 0,000), aroma (p = 0,000), consistency (p = 0,000), and flavor (P = 0,000)) which means there is a rosella juice influence on the receiving power of the juice. The receiving power of rosella juice that is preferred by panelist both in terms of color, aroma, consistency and flavor is on P2. In patients with diabetes mellitus can consume Rosella juice as much as 625 ml/day with vitamin C content of 25 mg.